In situ analysis of shear bands and boundary layer formation in metals - Yadav, Shwetabh (Proc Math Phys Eng Sci, 2020)
Shear banding is a plastic instability in large deformation of solids where the flow becomes concentrated in narrow layers, with broad implications in materials processing applications and dynamic failure of metals. Given the extremely small length and time scales involved, several challenges persist in studying the development of shear bands. Here, we present a new approach to study shear bands at low speeds using low melting point alloys. We use in situ imaging to directly capture the essential features of shear banding, including transition from homogeneous to shear banded flow, band nucleation and propagation dynamics, and temporal evolution of the flow around a developing band. High-resolution, time-resolved measurements of the local displacement and velocity profiles during shear band growth are presented. The experiments are complemented by an analysis of the shear band growth as a Bingham fluid flow. It is shown that shear banding occurs only beyond a critical shear stress and is accompanied by a sharp drop in the viscosity by several orders of magnitude, analogous to the yielding transition in yield-stress fluids. Likewise, the displacement field around a nucleated band evolves in a manner that resembles boundary layer formation, with the band thickness scaling with time as a power law.